Healing efficiency characterization of self-repairing polymer composites based on damage continuum mechanics. (15th January 2019) - Tan, P.S.; Somashekar, A.A.; Casari, P.; Bhattacharyya, D.
Abstract: Self-healing polymer composites are part of a class of materials which have the capability to repair themselves when damaged. They are often tested by inflicting damage onto them and then performing a mechanical test to initiate and measure self-healing. Self-healing efficiency is commonly defined as the ratio of a recovered property value to its original value. Applying this in practice can be challenging as most self-healing experiments are idealized scenarios. In this work, microcapsules containing epoxy and mercaptan self-healing agents were incorporated into ±45° composite weaves that were subjected to cyclic tensile loading and unloading. A damage mechanics theory was applied to quantify the change in stiffness and determine self-healing effectiveness. As this method did not enable a direct comparison between the damaged and healed states of the material, a new methodology was developed to take into account the energy levels of the material in order to quantify self-healing performance.